Utilization of Digitalization in Improving the Quality of Services and Information in Sumurkondang Village, Cirebon - Merlinda Intan Fauziah; Fajar Nurjaman; Rayhan Syawal Firizki; Elvira Fitriyanti; Alif Suryalaksana (Publikasi Indonesia, 2025)
Digitalization plays a transformative role in improving public service delivery and information dissemination, particularly in rural areas. This study explores the implementation of digitalization in Sumurkondang Village, Cirebon, and its effects on administrative efficiency, accessibility, and community involvement. Employing a qualitative approach with a descriptive case study design, the research involved in-depth interviews, participatory observations, and document analysis. The findings reveal that digitalization improves service quality and ease of access, particularly among younger residents. However, challenges such as low digital literacy among older populations, limited infrastructure, and lack of awareness hinder widespread adoption. Despite some basic digital training conducted by the village government, participation remains low, and skepticism toward digital platforms persists among older users. The study concludes that while digitalization holds great promise for rural development, its success depends on inclusive training, stronger infrastructure, and active community engagement. Recommendations include targeted digital literacy programs, improved internet access, and collaborative efforts between local governments and external partners. These efforts can foster sustainable digital transformation and serve as a model for similar rural communities in Indonesia.